Enhanced mechanical properties of polymer-modified cementitious materials via organosilane fly ash hybrid–polyvinyl pyrrolidone crosslink network. (2nd May 2022) - Zhao, Du; Wang, Fazhou; Liu, Peng; Hu, Shuguang; Hu, Chuanlin; Yang, Lu
Graphical abstract: Highlights: Organosilane-fly ash hybrid was prepared. A strong network is formed through PVP and hybrid crosslinking. The compressive strength of polymer-modified cementitious material was enhanced. The homogeneous distribution of FA by agitation helps disperse the polymer evenly. The micro-mechanical properties of cement mortar were greatly enhanced. Abstract: Low compressive strength has always been a problem for polymer-modified cementitious materials. In this paper, a crosslinking network that makes use of organosilane-fly ash (FA) hybrid and polyvinylpyrrolidone (PVP) was exploited to improve the compressive strength of polymer-modified cementitious materials. Two kinds of polymers and five different organosilanes with different functional groups were investigated. The best improvement was realized when aminosilane (–NH2 ) or mercaptosilane (–SH) was used. The mechanism of the enhanced compressive strength was investigated extensively. A strong network is formed through the chemical connection between polymer, FA, organosilane, and calcium-silicate-hydrate (C-S-H). The cement paste has significantly enhanced micro-mechanical properties according to the nanoindentation testing results and the pore structure shows obvious improvement in the mercury intrusion porosimetry results. The presented strategy can thus effectively increase the compressive strength of polymer-modified cementitious materials without adverse effects.